The choroid plexus in health and in disease: dialogues into and out of the brain - Marques, Fernanda (2017)
This article brings the choroid plexus into the context of health and disease. It is remarkable that the choroid plexus, composed by a monolayer of epithelial cells that lie in a highly vascularized stroma, floating within the brain ventricles, gets so little attention in major physiology and medicine text books and in the scientific literature in general. Consider that it is responsible for producing most of the about 150 mL of cerebrospinal fluid that fills the brain ventricles and the subarachnoid space and surrounds the spinal cord in the adult human central nervous system, which is renewed approximately 2-3 times daily. As such, its activity influences brain metabolism and function, which will be addressed. Reflect that it contains an impressive number of receptors and transporters, both in the apical and basolateral sides of the epithelial cells, and as such is a key structure for the communication between the brain and the periphery. This will be highlighted in the context of neonatal jaundice, multiple sclerosis and Alzheimer's disease. Realize that the capillaries that irrigate the choroid plexus stroma do not possess tight junctions and that the blood flow to the choroid plexus is five times higher than that in the brain parenchyma, allowing for a rapid sensing system and delivery of molecules such as nutrients and metals as will be revised. Recognize that certain drugs reach the brain parenchyma solely through the choroid plexus epithelia, which has potential to be manipulated in diseases such as neonatal jaundice and Alzheimer's disease as will be discussed. Without further notice, it must be now clear that understanding the choroid plexus is necessary for comprehending the brain and how the brain is modulated and modulates all other systems, in health and in disease. This review article intends to address current knowledge on the choroid plexus, and to motivate the scientific community to consider it when studying normal brain physiology and diseases of the central nervous system. It will guide the reader through several aspects of the choroid plexus in normal physiology, in diseases characteristic of various periods of life (newborns-kernicterus, young adults-multiple sclerosis and the elder Alzheimer's disease), and how sex-differences may relate to disease susceptibility.